Measuring process innovation outputs and understanding their implications for firms and workers: Evidence from Pakistan. - Waqar Wadho; Azam Chaudhry (Global Labor Organization (GLO), 2024)
New processes significantly affect firms and workers; however, due to a lack of quantitative indicators, our understanding of the measures, determinants, and impacts of new processes remains limited. Drawing on unique data from Pakistan, we analyzed five different measures of process innovation output: cost reductions, defect rate reductions, reductions in production cycle time, increases in production capacity, and improvement in product quality. We find that the breadth and depth of innovative capabilities, level of competition, and availability of market sources of knowledge are important inducers of process innovation and that smaller firms are more likely to introduce new processes and are better able to transform them into higher output. All five process innovation outputs are associated with higher labor productivity and higher sales. We do not find that adopting new processes led to labor displacement; however, there is suggestive evidence that new processes led to the increased employment of skilled workers.
Keywords: O31; O32; O33; J23; J24; 330; Technology; Innovation; Process innovation; Cost-reduction; Labor productivity; Developing countries; Textiles & Apparel; Pakistan